Wound dressing based on banana peels waste and chitosan by strengthening lignin as wound healing medicine - Teuku Rihayat, Teuku Rihayat; Suryani, Suryani; Siregar, Januar Parlaungan; Zaimahwati, Zaimahwati; Salmyah, Salmyah; Helmi, Helmi; Sariadi, Sariadi; Fitria, Fitria; Satriananda, Satriananda; Alfian Putra, Alfian Putra; Zahra Fona, Zahra Fona; Juanda, Juanda; et al. (2019)
Recent studies in new applications of wound dressing offer and promote the process of wound healing. The purpose of this study was to develop lignin-based wound dressing on banana peel and then put it into chitosan film for wound dressing applications. The use of banana peels helps the formation of skin compounds so that they can be used to treat better wounds. Banana peel added to chitosan as matrix filler with concentration (0, 1, 3, 5, 7, 10% wt), then the dressing membrane swelling in 48 hours is at 0% wt 120.5931%, at 1% wt 99. 9981%, 3% wt 79.2916%, 5% wt is 68.1819%, 7% wt is 61.9173% and 10% wt is 45.3981%. Fourier Transform Infrared (FTIR) test, Scanning Electron Microscopy (SEM), swelling properties were carried out to characterize the prepared film. Antimicrobial tests were carried out by disc diffusion method and film growth inhibitory effects including different amounts studied in Escherichia coli and Staphylococcus aureus. FTIR at a concentration of 7% wt showed that there was an interaction between banana peel and chitosan on the absorption band 3185,728 cm-1. In SEM the best sample morphology structure at 5% wt shows a good interface interface. Addition of banana peel as lignin decreases the level of swelling of water in wound dressing. In addition, Staphylococcus aureus is the most sensitive strain recorded in wound dressing. Banana skin which is included in chitosan film seems to be a potential and new biomaterial for wound healing applications.